Cognitive deficits and their relationship to other neurological complications in chronic alcoholic patients. Issue 10 (October 1984) - Franceschi, M; Truci, G; Comi, G; Lozza, L; Marchettini, P; Galardi, G; Smirne, S
Abstract : In randomly selected chronic alcoholics hospitalised for the first time for detoxification a high prevalence (68%) of cognitive deficits was found. Peripheral neuronal damage was seen in 74%, autonomic neuronal damage in 24%. Cognitive deficits were not correlated with age, daily ethanol intake, duration of alcohol abuse or severity of liver damage. There was no correlation of peripheral, autonomic and central nervous system damage. Alcohol-induced damage of the nervous system is a common complication of chronic alcoholism, whose clinical importance often obscures possible concomitant liver damage.